2011
DOI: 10.3109/08820139.2011.575426
|View full text |Cite
|
Sign up to set email alerts
|

Expression of Th17 and Treg Lymphocyte Subsets in Hypertrophied Adenoids of Children and its Clinical Significance

Abstract: Adenoid hypertrophy is the most common cause of upper airway obstruction and sleep-disordered breathing in children, yet its pathogenesis remains unclear. The identification of the novel helper T cell subsets, Th17 cells and regulatory T cells (Tregs) could provide new insight into our understanding of the mechanisms involved in the development of this condition. The purpose of this study is to evaluate the adenoidal lymphocyte subsets to describe the percentage of various lymphocyte subsets in hypertrophied a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
12
1
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(15 citation statements)
references
References 32 publications
1
12
1
1
Order By: Relevance
“…Sade et al evaluated the adenoidal lymphocyte subsets to describe the percentage of various lymphocyte subsets in hypertrophied adenoids of children and correlated them with symptom severity. They found a significant negative linear correlation between the Th17/Treg ratio and the patients' clinical scores independent of age and gender [24]. Apparently, our observation was opposite to the results of Sade.…”
Section: Discussioncontrasting
confidence: 99%
“…Sade et al evaluated the adenoidal lymphocyte subsets to describe the percentage of various lymphocyte subsets in hypertrophied adenoids of children and correlated them with symptom severity. They found a significant negative linear correlation between the Th17/Treg ratio and the patients' clinical scores independent of age and gender [24]. Apparently, our observation was opposite to the results of Sade.…”
Section: Discussioncontrasting
confidence: 99%
“…In this regard, Sade et al investigated the Th17 and Treg expression in hypertrophied adenoids. 38 These authors found a significant negative linear correlation between Th17/Treg ratio and the clinical severity in 20 children undergoing adenoidectomy. This result might have great pathophysiological relevance, because allergic inflammation is characterized by Th17 overexpression 39 and defective Treg function.…”
Section: Discussionmentioning
confidence: 94%
“…Treg cells expressing the forkhead/winged helix transcription factor (Foxp3) orchestrate the overall immune response and play a role in immune tolerance through contact-dependent suppression or by regulating the activity of the effector T cells or releasing antiinflammatory cytokines, such as interleukin-10 (IL-10) and transforming growth factor b (TGF-b1). Sade [7] found that the Th17/Treg ratio negatively correlates with the clinical score for OSA independent of age and gender. Jin Ye [8] found that the Th17/Treg ratio is elevated in patients with OSA and positively correlates with apnea-hypopnea index (AHI).…”
mentioning
confidence: 98%